Japanese and Local Partners Commitment to IJVs: Psychological Consequences of Outcomes and Investments in the IJV Relationships - Cullen, John B.; Johnson, Jean L.; Sakano, Tomoaki (Journal of International Business Studies, 1995)
This study investigated the antecedents of commitment in IJVs from the major partners' perspective. Data were gathered from Japanese and local partners in IJVs located in eleven countries and analyzed in structural equations models. Results indicated that commitment is largely a function of the perceived benefits of the relationship, i.e., satisfaction and economic performance. However, exploration analyses of differences between local partners and the Japanese suggest that the effects of psychological antecedents might be contingent on the strategic intent of the relationship.